ARABIA’S LAST FORESTS UNDER THREAT: PLANT BIODIVERSITY AND CONSERVATION IN THE VALLEY FOREST OF JABAL BURA (YEMEN) - Hall, M.; Al-Khulaidi, A. W.; Miller, A. G.; Scholte, P.; Al-Qadasi, A. H. (Edinburgh Journal of Botany, 2008)
The isolated massif Jabal Bura (Yemen) is home to the largest area of ‘valley forest’ in southwest Arabia’s western escarpment mountains. This study surveys the composition of this very rare forest and records the diversity of vascular plant species. It notes the valley forest as the home of several regionally rare species and records new locations for these taxa. A brief analysis of the canopy layer is provided, enabling comparisons with similar vegetation in northeast Africa. The paper discusses the importance of this regionally rare vegetation as well as threats to its conservation.